PEMAHAMAN DAN PEMANFAATAN HIMPUNAN DATA DALAM KEGIATAN BIMBINGAN DAN KONSELING DI SMK N I KECAMATAN SUTERA - Husnah, Fauzil - (Bimbingan dan Konseling, 2014)
Background of this research was there is a result of data collection that was not use maximal in counseling service. This research focused on: 1) counselor understanding to data collection, 2) the use of data collection by the counselor, 3) the obstacle counselor in using data. This is a qualitative research . the informant of this research were two counselor, coordinator and students. Data collected through the interview and documentation. The data of this research tested with used trianggulasi, membercheck and analyzed through three steps: 1. Reduction data, 2. Presenting data, 3. Conclusion. The result of this research showed that: 1) counselor understanding of data collection, 2) the use of data collection was not running well by the counselor, 3) there is no time to classical guidance service. This research recommended to counselor to increase their knowledge and perception about implementing guidance and counseling in data collection, the counselor should implementing data collection with effective and efficient.